Analisis Penataan Tempat Kerja Di Industri Pembuatan Sepatu ”X” Kota Semarang Berdasarkan Prinsip 5S (Seiri, Seiton, Seiso, Seiketsu, Shitsuke) - - Fathimah; Bina Kurniawan; Baju Widjasena (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2014)
5S is a culture about how people treat their workplace properly. If the workplace neat, clean, and orderly, then the ease of individual works can be created, and thus the 4 main targets industrial fields, namely efficiency, productivity, quality, and include safety and health that would be more easily achieved. Basically 5S is a process change in attitude by applying the arrangement and cleanliness of work, or in general is the Occupational Health and Safety ( K3 ). Based on a survey early, workers in this industry still not apply 5S in any stage of the work they do. This is evident from the less organized neat working environment there. The purpose of this study was analyze the arrangement of workplaces in the shoe-making industry